Effects of Energy Pricing on the Mining Sector Performance in South Africa: An Econometric Approach - Mmutle, Tumelo; Daw, Olebogeng David; Khobai, Hlalefang (International Journal of Energy Economics and Policy, 2022)
Mining plays a very substantial role in the economy of South Africa. This sector remains to be amongst the greatest consumers of energy in the country, especially electricity. It is against these background that the main objective of this study is to determine the effects of energy pricing on the mining sector performance in South Africa from 1990 to 2019. Johansen and ADRL procedures were used to determine the effects of energy pricing on the mining sector performance in South Africa. The results of the Error correction model (ECM) under Johansen cointegration technique are negative as expected but they are not statistically significant. The study error term is -0.122975, which meant that cointegration relationship is established. The results show that capital stock and labour play an important role in balancing mining productivity, while energy prices, Gross Domestic Product and import prices, on the other hand, play a lesser role in balancing mining productivity. The results of the Error correction model (ECM) under ARDL designate the short-run coefficient for D (LNCT) and D (GDP2) are statistically significant at 1% level and the coefficient of error correction term ecm (-1) valued at -1.037410 is negative and highly significant signifying that in the short-run changes in Capital stock and Gross Domestic Product are associated with mining production. The long-run relationship is illustrated by a negative sign on the coefficient of the ECT. Policy implication of a long-run optimistic relationship between electricity pricing and Mining Sector productivity is that mines should invest on producing their own energy, in that way they will be responsible for reducing their costs and that could results in mines increasing their productive capacity in the long-term.